Case Report: Decentralized trial of tolerability-adapted exercise therapy after severe Covid-19 - Scott, Jessica M.; Qiu, Zhuyu; Rahman, Jahan; Moskowitz, Chaya S.; Michalski, Meghan G.; Lehman, Sarah; Lee, Catherine P.; Harrison, Jenna; Yu, Anthony F.; Marouf, Amira; Vardhana, Santosha; Boutros, Paul C.; et al. (Frontiers in Immunology, 2025)
We assessed the safety, tolerability, and effects of exercise therapy in three patients with cancer and hospitalization for SARS-CoV-2 infection in an early-phase prospective trial. All study assessments and exercise sessions were conducted remotely (decentralized) in patient’s homes. Patients received five escalated doses of aerobic exercise therapy (range, 90 to 375 minutes per week) following a tolerability-based adapted schedule over 30 consecutive weeks. Exercise therapy was safe (i.e., no serious adverse events), tolerable (i.e., all exercise therapy doses were completed, with an overall average relative exercise dose intensity of 89%), and associated with improvements in patient physiology (e.g., exercise capacity) and patient-reported outcomes (e.g., quality of life). Correlative proteomic and single-cell immune sequencing of peripheral blood samples revealed marked alterations in protein and immune phenotypes implicated in post COVID-19 condition. (ClinicalTrials.gov number, NCT04824443).